Identification and Characterization of the Glucose-6-Phosphate Dehydrogenase Gene Family in the Para Rubber Tree, Hevea brasiliensis - Long, Xiangyu; He, Bin; Fang, Yongjun; Tang, Chaorong (Frontiers in Plant Science, 2016)
As the key enzyme in the pentose phosphate pathway (PPP), glucose-6-phosphate dehydrogenase (G6PDH) provides NADPH and intermediary metabolites for rubber biosynthesis, and plays an important role in plant development and stress responses. In this study, four Hevea brasiliensis (para rubber tree) HbG6PDH genes were identified and cloned using a genome-wide scanning approach. On the basis of phylogeny analysis and subcellular localization predictions, HbG6PDH3 is a cytosolic isoform, while the other three genes (HbG6PDH1, 2 and 4) are plastidic molecular variants. Enzyme activity assay and expression pattern analysis showed HbG6PDHs to be involved in latex regeneration, and to influence rubber production positively in the rubber tree. The cytosolic HbG6PDH3 is the predominant isoform in latex, implying a principal role for this isoform in controlling carbon flow and NADPH production in the pentose phosphate pathway during latex regeneration. The expression pattern of the plastidic HbG6PDH4 correlates well with the degree of tapping panel dryness, a physiological disorder that stops the flow of latex from affected rubber trees. In addition, the four HbG6PDHs responded to temperature change and drought stress in the root, bark and leaves, implicating their possible roles in maintaining redox balance and defending against oxidative stress.